Akulivikchuk: a nineteenth century Eskimo village on the Nushagak River, Alaska / Fieldiana, Anthropology, v. 60 - VanStone, James W.; Williams, Patricia M. editor Managing Editor, Scientific Publications ([Chicago] Field Museum Press, 1970)
Includes bibliographical references (p. 110-113). Fieldiana series has been published as Anthropological Series by Field Columbian Museum (1895-1909) and Field Museum of Natural History (1909-1943), and as Fieldiana: Anthropology by Chicago Natural History Museum (1945-1966) and Field Museum of Natural History (1966-).